Prospects for development of oil production in iraq base cognitive model in today’s geopolitical context - Tatiana A. Makarenya; Galina V. Gorelova; Ahmed Ibrahim Hussein Obaidi; Hussein Ahmed Ahmed Farid (Вестник ВГУ. Серия: Системный анализ и информационные технологии, 2023)
The Middle East has a high competitive advantage due to its large oil reserves, low cost and low production cost of the production process. The role of the Middle East in oil production should not be underestimated. In 2020, oil production in the Middle East will account for 34% of global oil production, and could exceed 50% in the future. One of the strongest players is Iraq, which has both oil and gas reserves, which are consumed by both neighboring countries and distant countries. The development of oil and gas production is influenced by both the economic and political situation inside and outside the country. Therefore, trends and prospects for the development of political and economic relations need to be analyzed in order to predict the development of the situation in the fuel and energy complex. The geography and productivity of oil fields in Iraq is different and depends on the specific field. In general, the economic situation in the purchasing countries, which are China, India, the USA and the political situation inside Iraq, influences the value of oil production. Therefore, the problem of long-term forecasting the behavior of oil producers is an interesting scientific and practical problem. The purpose of this article is to build a scenario of socio-economic development of Iraq using cognitive modeling by identifying key parameters and factors affecting them. A cognitive map has been made, which shows the main oil-producing areas of Iraq and the factors that determine the output of oil-producing provinces. As a result, we can state that taking into account certain factors and relationships, the cognitive map is structurally stable because it has an odd number of negative cycles (three). The use of cognitive maps can help build long-term plans for the development of enterprises of the fuel and energy complex of Iraq. Based on the results of the study, recommendations have been developed that can be used by government agencies to improve the efficiency of fuel and energy companies in Iraq located in different parts of the country. It also identified the most vulnerable regions that need to be prioritized for government support.